Inmate public autoerotism and hostile work environments: an examination of federal cases - Worley, Vidisha Barua (Journal of crime and justice, 2021)
In Hicks v. Alabama , the court ruled in favor of the prison agency when female correctional officers filed a suit against the state and several supervisors for sexual harassment by inmates. In the aforementioned case, the plaintiffs alleged that their superiors failed to control inmates from masturbating in their presence, which constituted a hostile work environment and disparate treatment in violation of Title VII. In this paper, we examine several legal cases over the last twenty years that have set the stage for changes in the prison workplace for female correctional officers. As our analysis reveals, when female correctional officers are sexually harassed by male inmates because of their gender, this creates a hostile work environment for these employees based on their membership in a protected class (here females). In such situations, where correctional administrators and supervisors deliberately fail to take corrective measures to address this issue of harassment by third parties, it creates the basis for Title VII suits, even though the employers themselves are not the perpetrators. This study has important implications for the contemporary management of prisons and jails.